2021
DOI: 10.5993/ajhb.45.6.10
|View full text |Cite
|
Sign up to set email alerts
|

Quarantine Hotels: Integration between Hospitality and Healthcare Services to Promote Health Behavior and Quality of Life

Abstract: Objectives: COVID-19 has spread globally and infected millions of people, thereby restricting their movement. Quarantine hotels play an important role in protecting people from COVID-19 and contribute to a better quality of life. The objective of this study was to examine the role of quarantine hotels in providing improved quality of life through both medical and hospitality services under one roof to address the COVID-19 situation in Saudi Arabia. Methods: This study used a quantitative, cross-sectional rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The occurrence of diseases has caused problems for the society and the health system 29-33 . The health system and services include education, prevention, care, screening, outpatient treatment, referral to health centers, and this type of management leads to improving the level of health in the community [34][35][36][37][38][39][40][41] . The results of a study in New Zealand showed that the factor of continuity of care scored higher in the evaluation conducted in health centers 42 .…”
Section: Componentsmentioning
confidence: 99%
“…The occurrence of diseases has caused problems for the society and the health system 29-33 . The health system and services include education, prevention, care, screening, outpatient treatment, referral to health centers, and this type of management leads to improving the level of health in the community [34][35][36][37][38][39][40][41] . The results of a study in New Zealand showed that the factor of continuity of care scored higher in the evaluation conducted in health centers 42 .…”
Section: Componentsmentioning
confidence: 99%
“… This study showed that timely communication, temporary reduction of working hours, and flexible work schedule are often some of the nonmonetary incentives that hospitals may adopt to increase staff motivation. Healthcare systems must take effective steps to make patients and health workers more satisfied and to improve the level of health services and care [14][15][16][17][18][19].…”
Section: Suggestionsmentioning
confidence: 99%